1996
DOI: 10.1093/bja/76.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pharmacodynamics and pharmacokinetics of an infusion of cis-atracurium (51W89) or atracurium in critically ill patients undergoing mechanical ventilation in an intensive therapy unit

Abstract: We have studied 12 critically ill, sedated patients who required a neuromuscular blocking drug to assist mechanical ventilation in an intensive care unit. Patients were randomized to receive an infusion of cis-atracurium 0.18 mg kg-1 h-1 (group 1, n = 6) or atracurium 0.6 mg kg-1 h-1 (group 2, n = 6) preceded, if necessary, by a bolus dose of 2 x ED95 of the same drug (cis-atracurium 0.1 mg kg-1 or atracurium 0.5 mg kg-1). Neuromuscular block was monitored using an accelerograph and the infusion rate adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 19 publications
4
25
1
Order By: Relevance
“…Cisatracurium ICU infusion studies (> 24-hr duration) suggest that there is marginal accumulation of the drug. Several studies suggest that the duration of action of cisatracurium is not affected by organ dysfunction (23). Laudanosine, a metabolite of atracurium, has central nervous system stimulating effects.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Cisatracurium ICU infusion studies (> 24-hr duration) suggest that there is marginal accumulation of the drug. Several studies suggest that the duration of action of cisatracurium is not affected by organ dysfunction (23). Laudanosine, a metabolite of atracurium, has central nervous system stimulating effects.…”
Section: Pharmacologymentioning
confidence: 99%
“…Laudanosine, a metabolite of atracurium, has central nervous system stimulating effects. Laudanosine levels have been reported to increase when using long-term atracurium infusions but are typically not high enough to promote seizure activity in humans (13,19,23).…”
Section: Pharmacologymentioning
confidence: 99%
“…This has already been attributed to an up-regulation of acetylcholine receptors, although some authors did not find the same results [13, 22]. The pharmacokinetics of NMBAs in critically ill patients can be affected by many conditions, such as sepsis and/or shock [12]. In addition, it has been shown that ICU patients are less sensitive to neuromuscular blockade than patients in the operating room [14].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits and limitations of TOF stimulation were primarily determined from studies performed in operative room patients [10, 11], with results that may not be generalizable to ICU patients. In critically ill patients, the duration of neuromuscular blockade is longer, sepsis and/or shock is often present, and pharmacokinetic is difficult to predict [1214]. Lastly, agreement between subjective and objective means of assessing the degree of neuromuscular blockade has been little studied in ICU [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing doses of cisatracurium can shorten the time to obtain a TOF = 0 [12-14]. ICU studies regarding the pharmacokinetics and pharmacodynamics of cisatracurium focused on patients receiving continuous infusions of cisatracurium [1] and mostly described the recovery profiles after continuous administration [21,22]. The doses used in those publications were a bolus of 0.1 mg.kg -1 (2 × ED95) with an average rate of infusion of 2.6 mg.kg -1 .min -1 (0.15 mg.kg -1 .h -1 ) or 3.2 mg.kg -1 .min -1 (0.19 mg.kg -1 .h -1 ) as required to obtain a sufficient degree of neuromuscular blockade for mechanical ventilation [21,22].…”
Section: Discussionmentioning
confidence: 99%